2019
DOI: 10.26618/exposure.v8i2.2785
|View full text |Cite
|
Sign up to set email alerts
|

Oral Corrective Feedback in Speaking Class: Its Frequency, Students’ Perceptions and Preference

Abstract: The objective of this qualitative study is to investigate kinds of corrective feedback used by the English lecturer in speaking class at English Department in one of private University in Jember. Further, this research also investigate how the students’ perception and preference lying on their speaking proficiency toward the corrective feedback which is dominantly used by the lecturer. Based on the analysis taken from questionnaire given to 30 students of English Language Education department, it was found tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…Furthermore, students could add their knowledge about speaking elements mistakes from feedback, such as grammar, vocabulary, pronunciation, flow of the speech, intonation, facial expression, and other elements in speaking. This result is line with the several studies from researchers who found that multimodal feedback is beneficial for several reasons namely constructive input for students in their performance and increase their ability (Phuong & Huan, 2018;Siska, Mukhaiyar & Ratmanida, 2018;Laeli & Setiawan, 2019;Ningkrum, 2019).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Furthermore, students could add their knowledge about speaking elements mistakes from feedback, such as grammar, vocabulary, pronunciation, flow of the speech, intonation, facial expression, and other elements in speaking. This result is line with the several studies from researchers who found that multimodal feedback is beneficial for several reasons namely constructive input for students in their performance and increase their ability (Phuong & Huan, 2018;Siska, Mukhaiyar & Ratmanida, 2018;Laeli & Setiawan, 2019;Ningkrum, 2019).…”
Section: Discussionsupporting
confidence: 90%
“…Thus, studies on perceptions on teachers' feedback showed that students had positive responses on corrective feedback (Muhsin, 2016;Asnawi, Zulfikar & Astila, 2017;Nemari, Alavi, Mohebbi, Masjedlou, 2017;Wang, Yu, & Teo, 2018;Muyashoha, & Sugianto, 2019). Besides, types of corrective feedback were often researched by researchers because corrective feedback is essential to be known by the teacher, lecturer and student (Fadilah, Anugerahwati and Prayogo, 2017;Putri, 2018;Phuong & Huan, 2018;Siska, Mukhaiyar & Ratmanida, 2018;Laeli & Setiawan, 2019;Ningkrum, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The differennce lies on the level of students, while study by Zare et al, (2022) found that high proficiency students prefer recasting, this study found that high language awareness level students prefer explicit correction in receiving OCF. Thus, the result of students' feedback preference is also supported by Laeli & Setiawan (2019) which students prefer to receive explicit correction. The different aspect is on the setting of the study that this study done in junior high school while (Laeli & Setiawan, 2019) setting of study is in university.…”
Section: Discussionmentioning
confidence: 82%
“…Thus, the result of students' feedback preference is also supported by Laeli & Setiawan (2019) which students prefer to receive explicit correction. The different aspect is on the setting of the study that this study done in junior high school while (Laeli & Setiawan, 2019) setting of study is in university. Explicit correction preference in this study is also supported by Van Ha et al (2021) that high school sudent prefer to receive explicit correction.…”
Section: Discussionmentioning
confidence: 82%
“…Questioning and Assessment for Learning (AfL) are inseparably related. Following the pattern of IRF/E as claimed by (Ganapathy, Ai, Tan, & Phan, 2020;Laeli & Setiawan, 2019;Lee, Mak, & Burns, 2015;Nassaji, 2016), teacher questioning is widely acknowledged as crucial technique in classroom discourse and is used evaluate the specific learning goals (Black & Wiliam, 2009;Gattullo, 2000;Jiang, 2014;Milawati, 2017;Widiastuti & Saukah, 2017). Focusing on feedback activity, teachers utilize questions to make their students more active resulting from meaning negotiation process both through explicit and implicit.…”
Section: Introductionmentioning
confidence: 99%